2019
DOI: 10.35940/ijrte.b1034.0982s919
|View full text |Cite
|
Sign up to set email alerts
|

Work-Life Quality, Job Involvement, and Affective Commitment of School Teachers

Abstract: The purpose of this study is to examine the influence of work-life quality and job involvement perceived by teachers to their affective commitment so that they feel a strong emotional bond to their work and school organization, are able to identify the goals and values of the school organization well, and really want to be there. This research uses causal survey method by using path analysis technique. This study uses the sample from 138 teachers in eight buddhist senior high schools in Jakarta, which were sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Leadership is a tender process in giving reciprocal influence which combines thoughts, feelings, and actions. This yields cooperation in serving the goals which are embraced by both of the parties -the leader and the followers (Bolman & Deal, 2008;Burmansah, Sujanto, & Mukhtar, 2019). The realization of leadership activities in a group and sharing activities in teams is essential in terms of leadership actions (Ersozlu, 2016).…”
Section: Leadershipmentioning
confidence: 99%
“…Leadership is a tender process in giving reciprocal influence which combines thoughts, feelings, and actions. This yields cooperation in serving the goals which are embraced by both of the parties -the leader and the followers (Bolman & Deal, 2008;Burmansah, Sujanto, & Mukhtar, 2019). The realization of leadership activities in a group and sharing activities in teams is essential in terms of leadership actions (Ersozlu, 2016).…”
Section: Leadershipmentioning
confidence: 99%
“…Teacher work-life quality is defined as the integration of work roles and social roles so that the two can synergize effectively [ 31 ]. Efforts that school administrators can make to improve the quality of work life include developing programs that attract and retain competent teachers, improving school performance, creating healthy and safe working conditions, increasing teacher abilities, improving the balance of work and personal life aspects, increasing salaries and appropriate allowances, as well as regulating the balance of teachers' working hours.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Apart from that, the sense of employee ownership is also increasing, which is an important element for an organization, and this is influenced by leadership [ 30 ]. Burmansah et al [ 31 ] revealed that the quality of work life is positively and significantly related to teachers' affective commitment in schools. Alzamel et al [ 32 ] stated that OC is a form of loyalty to the company's beliefs and goals, dependency, and an ethical obligation to remain in the organization, where this OC can be improved through the QWL.…”
Section: Introductionmentioning
confidence: 99%
“…1a) from the Academic Dental Hospital, Universitas Airlangga, Surabaya, with good quality and has been confirmed by a radiologist. In this research, the sample size used was 38 panoramic radiographs for testing [11], and 106 panoramic radiographs for modeling. The role of the radiologist is to select a dataset according to the selection criteria.…”
Section: A Datasetmentioning
confidence: 99%